Antidepressant Adherence and Risk of Coronary Artery Disease Hospitalizations in Older and Younger Adults with Depression. Issue 7 (2nd June 2014) - Cooper, Denise C.; Trivedi, Ranak B.; Nelson, Karin M.; Reiber, Gayle E.; Eugenio, Evercita C.; Beaver, Kristine A.; Fan, Vincent S.
<x xml:space="preserve">Abstract</x> Objectives To assess whether the relationship between antidepressant adherence and coronary artery disease (CAD) hospitalizations varied between older and younger adults with depression. Design Retrospective cohort study. Setting Department of Veterans Affairs outpatient clinics nationwide. Participants Chronically depressed individuals (n = 50, 261; aged 20–97) who had been prescribed an antidepressant were identified from records indicating an outpatient clinic visit for depression (index depression visit) during fiscal years 2009 and 2010. Individuals were considered chronically depressed if they had had prior depression visits and treatment for depression within the previous 4 months. The sample was age‐stratified into younger (<65) and older (≥65) groups. Measurements After the index depression visit, medication possession ratios were calculated from pharmacy refill data to determine whether participants had 80% or greater adherence to antidepressant refills during a 6‐month treatment observation period. International Classification of Diseases, Ninth Revision, codes were used to derive CAD‐related hospitalizations during the follow‐up period. Mean follow‐up was 24 months. Data were analyzed using Cox proportional hazard models. Results Older participants with 80% or greater antidepressant adherence had 26% lower risk of CAD hospitalizations (hazard ratio = 0.74, 95% confidence interval = 0.60–0.93). Antidepressant adherence was not significantly related to CAD hospitalizations in younger adults. Conclusion Older adults with chronic depression with 80% or greater antidepressant adherence had significantly lower risk of CAD hospitalizations at follow‐up than those with less than 80% adherence. These preliminary results suggest that older adults with depression may derive cardiovascular benefits from clinical efforts to increase antidepressant adherence.